2021
DOI: 10.3389/fgene.2021.764245
|View full text |Cite
|
Sign up to set email alerts
|

Roles of HMGBs in Prognosis and Immunotherapy: A Pan-Cancer Analysis

Abstract: Background: High mobility group box (HMGB) proteins are DNA chaperones involved in transcription, DNA repair, and genome stability. Extracellular HMGBs also act as cytokines to promote inflammatory and immune responses. Accumulating evidence has suggested that HMGBs are implicated in cancer pathogenesis; however, their prognostic and immunological values in pan-cancer are not completely clear.Methods: Multiple tools were applied to analyze the expression, genetic alternations, and prognostic and clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…59 Another study analyzed the role of HMGB protein family in various tumors. 60 The results showed that HMGBs were highly expressed in various tumors, including COAD, DLBC, LGG, PAAD, READ, STAD and THYM. High HMGB1 expression was associated with worse OS in ACC and KICH and higher OS in THYM.…”
Section: Discussionmentioning
confidence: 96%
“…59 Another study analyzed the role of HMGB protein family in various tumors. 60 The results showed that HMGBs were highly expressed in various tumors, including COAD, DLBC, LGG, PAAD, READ, STAD and THYM. High HMGB1 expression was associated with worse OS in ACC and KICH and higher OS in THYM.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, RAC3 was significantly upregulated in tumor samples and exhibited widespread CNV alterations. HMGB3 was found to be overexpressed in a variety of cancers, including breast invasive carcinoma, sarcoma, skin cutaneous melanoma, ovarian serous cystadenocarcinoma, and acute myeloid leukemia (53,54). The upregulation of the HMGB3 gene has been implicated in tumorigenesis and chemotherapy resistance via various mechanisms (54).…”
Section: Discussionmentioning
confidence: 99%
“…High TMB score was associated with the poor prognosis of PAAD patients ( Li L. et al, 2021 ). Meanwhile, high TMB could increase the emergence of neoantigens, thereby enhancing immunotherapy response ( Lin et al, 2021 ). In this study, we found ceRNA risk score was positively associated with TMB score.…”
Section: Discussionmentioning
confidence: 99%